Biocontrol by Fusarium oxysporum Using Endophyte-Mediated Resistance - de Lamo, Francisco J.; Takken, Frank L. W. (Frontiers in Plant Science, 2020)
Interactions between plants and the root-colonising fungus Fusarium oxysporum (Fo) can be neutral, beneficial or detrimental for the host. Fo is infamous for its ability to cause wilt, root- and foot-rot in many plant species, including many agronomically important crops. However, Fo also has another face; as a root endophyte, it can reduce disease caused by vascular pathogens such as Verticillium dahliae and pathogenic Fo strains. Fo also confers protection to root pathogens like Pythium ultimum, but typically not to pathogens attacking above-ground tissues such as Botrytis cinerea or Phytophthora capsici. Endophytes confer biocontrol either directly by interacting with pathogens via mycoparasitism, antibiosis or by competition for nutrients or root niches, or indirectly by inducing resistance mechanisms in the host. Fo endophytes such as Fo47 and CS-20 differ from Fo pathogens in their effector gene content, host colonisation mechanism, location in the plant and induced host-responses. Whereas endophytic strains trigger localised cell death in the root cortex, and transiently induce immune signalling and papilla formation, these responses are largely suppressed by pathogenic Fo strains. The ability of pathogenic strains to compromise immune signalling and cell death is likely attributable to their host-specific effector repertoire. The lower number of effector genes in endophytes as compared to pathogens provides a means to distinguish them from each other. Co-inoculation of a biocontrol-conferring Fo and a pathogenic Fo strain on tomato prevents disease, and although the pathogen still colonises the xylem vessels this has surprisingly little effect on the xylem sap proteome composition. In this tripartite interaction the accumulation of just two PR proteins, NP24 (a PR-5) and a -glucanase, was affected. The Fo-induced resistance response in tomato appears to be distinct from Induced Systemic Resistance (ISR) or Systemic Acquired Resistance (SAR), as the phytohormones jasmonate, ethylene and salicylic acid are not required. In this review, we summarise our molecular understanding of Fo-induced resistance in a model and identify caveats in our knowledge.